Monopoly and Ikhtikar in Islamic Economics - Al Arif, M. Nur Rianto (Shirkah: Journal of Economics and Business, 2016)
Monopoly is a form of market imperfection, which does not occur in a competitive market. Ikhtikar is a form of market distortion caused by the occurrence of engineering in the market. Monopoly, from the perspective of Islamic economics, differs from ikhtikar. There are several criteria that must be met in order for an economic action to fulfill the category of ikhtikar. In Islamic economics, it is prohibited for a producer to deliberately engineer, either by hoarding or proporting scarcity, to obtain greater profits as price becomes more expensive. In Islamic economics, a monopoly is permitted, though monopolies can not charge rent. The government must take an effective role in preventing market distortion to maximize the wellbeing of society. Keywords: ikhtikar, monopoly, government’s role, islamic economics